Parental Supervision Of Children’s Learning In RW 4 Ulak Karang Selatan Sub-District - Septiana, Febby; Syur'aini, Syur'aini (Universitas Negeri Padang, 2024)
This research was motivated by parental supervision of children's learning in RW 4, Ulak Karang Selatan Subdistrict, which aims to find out how parents supervise children's learning. The research used is qualitative research. This approach uses descriptive qualitative because the problems to be discussed in this research are in the form of words, both written and spoken, not related to numbers. The results of this research show that, (1) Parental supervision of children's learning in RW 4, Ulak Karang Selatan Subdistrict, that is, parents are responsible for supervising and directing children's learning activities. (2) Parental Supervision Patterns Regarding Children's Learning in RW 4, Ulak Karang Selatan Subdistrict, namely the efforts of fathers and mothers in supervising, paying attention, assessing all children's activities whether they have been carried out correctly or not and with this supervision pattern parents supervise children in learning . (3) Forms of parental supervision regarding children's learning in RW 4, Ulak Karang Selatan Subdistrict, namely what form of supervision is carried out by parents over children when children are studying, whether parents guide and help children in learning and whether parents fulfill children's learning needs and provide motivation. children's learning.Keywords: Supervision, Parents, Learning